Preparation method of efficient, quick-acting and long-acting hydroxyapatite implantation spongy agent
By using colloidal solution of sodium hyaluronate and phosphate in hydroxyapatite implanted sponge agent, and aging and crosslinking, the stability of HAP particles in the preparation and use process is solved, achieving high efficiency, Quick and long-term unity.
Patent Information
- Application Number
- CN202411334353.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2025-02-14
AI Technical Summary
In the prior art, hydroxyapatite (HAP) particles need to be separated in solid-liquid during preparation, and are easily re-aggregated during storage and use, resulting in unstable dispersion and difficult to achieve high efficiency, quick effect and long-term unity.
By preparing a colloidal solution containing sodium hyaluronate and phosphate and aged and crosslinked under specific pH and temperature conditions, a stable collagen-hydroxyapatite complex is avoided. Aggregate and precipitate.
The high efficiency, quick effect and long-term uniformity of hydroxyapatite implanted sponge agent is achieved, and the stability of HAP particles in the preparation and use process is overcome, and the effect of slow release is improved.
Abstract
Description
Technical Field
[0001] A method for preparing a hydroxyapatite implant sponge. Specifically, the invention relates to a method for preparing a highly effective, fast-acting and long-acting hydroxyapatite implant sponge. Technical Background
[0002] Medical grade hydroxyapatite (HAP) microspheres have been widely used in the medical and biological fields due to their special structure and chemical composition. They are mainly used in bone repair, implant support, drug sustained release, etc.
[0003] Chinese patent 1CN109381745A discloses a collagen coral hydroxyapatite composite bone filling scaffold material and a method for preparing the same, comprising the steps of cutting and homogenizing a collagen sponge to prepare a slurry, mixing coral hydroxyapatite particles with the collagen slurry to obtain a collagen coral hydroxyapatite mixed slurry; placing the slurry into a mold for compression and dehydration, freeze drying to obtain a freeze-molded collagen coral hydroxyapatite scaffold; and performing a thermal cross-linking treatment to obtain a final collagen coral hydroxyapatite composite scaffold; through the technical solution, the coral hydroxyapatite particles are perfectly composited with collagen, the coral hydroxyapatite particles are strictly bound, and the shaping problem of the coral hydroxyapatite particles is solved, so that the collagen can still maintain a certain mechanical support under a physiological environment, and a bone filling scaffold material with good biocompatibility and bioactivity is prepared.
[0004] The coral hydroxyapatite particles in Chinese Patent 1 are relatively large, making it difficult to achieve high efficiency and rapid effect.
[0005] Chinese patent 2CN116103776A discloses a long-acting collagen fiber and its preparation method. This invention patent prepares collagen fibers with precisely controlled morphology through an in vitro 3D reconstruction process of collagen fibers. The collagen fibers are orderly arranged and evenly distributed, with a fiber diameter of 60-120nm, and the pore size of the formed fiber 3D network is 200-220μm; the long-acting collagen fibers prepared by the present invention not only provide a good growth environment for cells, but also have excellent stability and significantly enhanced resistance to enzymatic hydrolysis; the long-acting collagen fibers prepared by the method described in the present invention can be used in implants, artificial skin, artificial cartilage, hemostatic sponges, scaffold materials, medical devices and other fields.
[0006] We found that the combined use of Chinese Patents 1 and 2 is difficult to achieve long-term effects.
[0007] Compared with bulk or micron HAP, nano-hydroxyapatite HAP has a larger specific surface area and exhibits higher performance. However, nano-HAP is prone to agglomeration during preparation, use and storage, resulting in performance loss and limiting its use effect, such as difficulty in achieving slow release or long-term and high-efficiency unity.
[0008] The HAP particles currently prepared need to be separated from the solid and liquid and dispersed in the liquid again for use, which increases the process cost.
[0009] Therefore, in reality, it is necessary to overcome the trouble of solid-liquid separation of HAP particles during the preparation process, the trouble of re-aggregation during the preparation, storage and use, the trouble of re-dispersion in liquid, and the problem of poor stability of re-aggregation after dispersion.
[0010] In addition, the implant sponge containing hydroxyapatite can achieve the unity of high efficiency, rapid effect and long-term effect. Summary of the invention
[0011] Based on the above reasons, the purpose of the present invention is to provide a method for preparing a hydroxyapatite implant sponge, which overcomes the trouble of HAP (hydroxyapatite) particles needing to be separated from the solid and liquid during the manufacturing process and re-aggregating during the storage process after separation, as well as the trouble of needing to re-disperse HAP in liquid and the trouble of re-aggregating after dispersion. The preparation method can make the implant sponge achieve the unity of high efficiency, rapid effect and long-term effect.
[0012] The present invention relates to a method for preparing a highly effective, fast-acting and long-acting hydroxyapatite implant sponge, the method comprising:
[0013] 1) Disperse sodium hyaluronate with a molecular weight of 2000 to 10,000 (Daltons) in water, add calcium salt solution, mix well, and replace 40% to 70% (molar number) of sodium ions with calcium ions to form colloidal solution A, wherein the content or concentration of sodium hyaluronate in the solution is 10-30% wt / v;
[0014] 2) Adding 0.5-2 times the weight or volume of a sodium hyaluronate solution with a molecular weight of 200,000-500,000 (Daltons) to colloidal solution A to obtain colloidal solution B, wherein the content or concentration of sodium hyaluronate in the above sodium hyaluronate solution is 2-10% wt / v;
[0015] 3) Add a solution of phosphate or hydrogen phosphate or dihydrogen phosphate or a mixed salt thereof to the colloidal solution B, wherein the amount (molar number) of phosphate ions (or phosphorus) is 40% to 60% of the amount (molar number) of the above calcium ions, adjust the pH value to 10 to 11, mix well, and place in an environment at a temperature of 25-35° C. for 2-7 days to obtain a colloidal solution C;
[0016] 4) Adding calcium salt solution to colloidal solution C, wherein the amount (molar number) of calcium ions is 60% to 80% of the total amount (molar number) of positive ions in the above two hyaluronates, mixing, aging at room temperature 25-35° C. for 2-7 days, adjusting the pH value to 6.8-7.2, to obtain colloidal solution D;
[0017] 5) Filter the colloidal solution D through a nanofiltration membrane with a pore size of 200 Da to remove small molecules, thereby obtaining a colloidal solution E;
[0018] 6) Add 0.5-2 times the volume of 1-10% collagen and 0.5-2 times the volume of tyrosinase aqueous solution as that of colloid solution A to colloidal solution E, mix well, the ratio of the amount of tyrosinase to the collagen is 1-15U / g, keep the temperature at 0°C to 4°C for 24-72 hours, so that the collagen is basically cross-linked, and obtain colloidal solution F;
[0019] 7) The colloidal solution F is placed in a container so that the liquid layer thickness is 1-3 mm, and freeze-dried to remove the solvent. DETAILED DESCRIPTION
[0020] The content or concentration of the sodium hyaluronate with a molecular weight of 2000 to 10,000 Daltons is 20-25% wt / v.
[0021] The content or concentration of the sodium hyaluronate with a molecular weight of 200,000-500,000 Daltons is 4-8% wt / v.
[0022] The above calcium salts include but are not limited to calcium chloride, calcium acetate, calcium nitrate, calcium hydroxide or mixtures thereof.
[0023] The above-mentioned phosphates, hydrogen phosphates or dihydrogen phosphates include but are not limited to potassium salts, sodium salts and ammonium salts thereof.
[0024] The amount (molar number) of phosphate ions (or phosphorus) in the solution of the above-mentioned phosphate, hydrogen phosphate, dihydrogen phosphate or a mixed salt thereof is 50% to 55% of the amount (molar number) of calcium ions.
[0025] The above aging time is preferably 3-5 days.
[0026] The thickness of the liquid layer is preferably 1-2 mm.
[0027] The preparation method of the implant sponge of the present invention also includes further preparing it into a film, column, strip, plate, block, plug, pill, sheet, sponge or gel.
[0028] The advantage of using low molecular weight sodium hyaluronate in the present invention is that it maintains a relatively low viscosity at a higher concentration, which is conducive to the replacement of calcium ions by sodium ions in the center, and is conducive to increasing the calcium content. When using medium and high molecular weight sodium hyaluronate, it is easy to cause the sodium ions in the surface layer to be replaced by calcium ions to form a relatively viscous boundary layer, which hinders the replacement of sodium ions and calcium ions in the inner layer, and is not conducive to increasing the calcium content and uniform dispersion.
[0029] The present invention retains a portion of sodium ions in sodium hyaluronate instead of being completely replaced by calcium ions, which is beneficial to maintaining its relatively high hydrophilicity, and the viscosity is not particularly large, and it is not easy to cause aggregation or precipitation, thereby avoiding causing the release of hydroxyapatite to become uncertain.
[0030] The present invention adopts sodium hyaluronate with medium to high molecular weight, which is conducive to delaying the expansion of hydroxyapatite lattice and preventing the formation of larger hydroxyapatite particles; at the same time, it maintains a relatively high viscosity, which is conducive to the slow release of hydroxyapatite. Sodium hyaluronate with medium and small molecular weight has low viscosity, which is not conducive to sustained release, and may cause hydroxyapatite aggregation or precipitation, resulting in uncertainty in the release of hydroxyapatite. High molecular weight sodium hyaluronate is not conducive to the formation of hydroxyapatite. Specifically, because the viscosity is too high, the combination of phosphate ions and calcium ions slows down, resulting in a long reaction time or incomplete reaction. In addition, high viscosity sodium hyaluronate is easy to precipitate or aggregate after calcification.
[0031] When the present invention ages hydroxyapatite, calcium salt solution is added to calcify most of the positive ions in the hyaluronate, which can make the viscosity moderate and not too large or too small, which is conducive to preventing the hydroxyapatite from aggregating and is conducive to its slow release. The positive ions of a smaller part are calcified, which is not conducive to further preventing the hydroxyapatite lattice from expanding due to the smaller viscosity, and is not conducive to preventing the formation of larger hydroxyapatite particles, thereby being not conducive to the rapid release of the base apatite to achieve the purpose of high efficiency and quick effect, and may cause the release of hydroxyapatite to become uncertain. If all the positive ions are calcified, the water solubility of the hyaluronate will be greatly reduced, and it may easily cause the hyaluronate to aggregate or precipitate, and the release of the hydroxyapatite will become uncertain.
[0032] After the hydroxyapatite is formed, the collagen is mixed with other components and cross-linked, so that the hydroxyapatite can be further wrapped and isolated, which is conducive to further preventing the hydroxyapatite lattice from expanding and preventing the formation of larger hydroxyapatite particles, thereby facilitating the rapid release of the base apatite to achieve the purpose of high efficiency and rapid effect; and it is conducive to the further wrapped and isolated hydroxyapatite to be slowly released better, and to cooperate with sodium calcium hyaluronate for sustained release, so as to achieve the purpose of long-term effect. If the collagen is cross-linked in advance and then mixed with the hydroxyapatite and other components, the wrapping effect of the hydroxyapatite particles is not good, the effect of preventing the further aggregation is not good, and the sustained release effect is not good, and it is difficult to achieve the unity of high efficiency, long-term effect and rapid effect.
[0033] The advantages of the present invention over the prior art are:
[0034] 1) It overcomes the trouble of HAP particles needing solid-liquid separation during the preparation process and reaggregation during the preparation, storage and use process;
[0035] 2) It overcomes the trouble of HAP particles needing to be redispersed in the liquid;
[0036] 3) and overcome or delay the trouble of HAP particles reaggregating after dispersion;
[0037] 4) Achieve high efficiency, rapid effect and long-term effect
[0038] Example
[0039] The following non-selective examples, i.e., methods for preparing implants, further describe preferred embodiments within the scope of the present invention. There are many variations of these embodiments within the scope of the present invention.
[0040] Example 1
[0041] 1) Disperse sodium hyaluronate with a molecular weight of 2000 to 10,000 (Daltons) in water, add 5% calcium acetate solution, mix well, and replace 40% (molar number) of sodium ions with calcium ions to form colloidal solution A, in which the content or concentration of sodium hyaluronate is 25% wt / v;
[0042] 2) Add 1.5 times the weight of a sodium hyaluronate solution with a molecular weight of 200,000-500,000 (Daltons) to colloidal solution A, mix well, and obtain colloidal solution B, wherein the content or concentration of sodium hyaluronate in the above sodium hyaluronate solution is 4% wt / v;
[0043] 3) Add 5% potassium hydrogen phosphate solution to colloidal solution B, wherein the amount (molar number) of phosphate ions (or phosphorus) is 60% of the amount (molar number) of the above calcium ions, adjust the pH value to 10 to 11, mix well, and place in an environment at a temperature of 25-35° C. for 7 days to obtain colloidal solution C;
[0044] 4) Add 5% wt / v calcium acetate solution to colloidal solution C, wherein the amount (molar number) of calcium ions is 75% of the total amount (molar number) of positive ions in the above two hyaluronates, mix well, age at room temperature 25-35° C. for 4 days, and adjust the pH value to 6.8-7.2 to obtain colloidal solution D;
[0045] 5) Filter the colloidal solution D through a nanofiltration membrane with a pore size of 200 Da to remove small molecules, thereby obtaining a colloidal solution E;
[0046] 6) Add 1 volume of 3% collagen and 1 volume of tyrosinase aqueous solution to colloidal solution E, mix well, the ratio of tyrosinase to collagen is 5U / g, keep the temperature at 0°C to 4°C for 48 hours, so that the collagen is basically cross-linked, and obtain colloidal solution F;
[0047] 7) The colloidal solution F is placed in a container so that the liquid layer thickness is 1.5 mm, and freeze-dried to remove the solvent.
[0048] Comparative Example 1-1
[0049] In Example 1, about 40% (in moles) of sodium ions are replaced by calcium ions to form colloidal solution A.
[0050] Replace with
[0051] About 100% (in moles) of sodium ions are replaced by calcium ions to form colloidal solution A.
[0052] and
[0053] A 5% potassium hydrogen phosphate solution was added to the colloidal solution B, wherein the amount (molar number) of phosphate ions (or phosphorus) was the same as that of the phosphate ions (or phosphorus) in Example 1, and the other parameters remained unchanged.
[0054] Comparative Example 1-2
[0055] The content or concentration of sodium hyaluronate in the sodium hyaluronate solution (200,000-500,000 Daltons) in Example 1 is replaced with a content or concentration of sodium hyaluronate in the sodium hyaluronate solution (200,000-500,000 Daltons) of 0.4% wt / v, and the rest remain unchanged.
[0056] As in Example 1-3
[0057] The content or concentration of sodium hyaluronate in the sodium hyaluronate solution (200,000-500,000 Daltons) in Example 1 is replaced with a content or concentration of sodium hyaluronate in the sodium hyaluronate solution (200,000-500,000 Daltons) is 16% wt / v, and the rest remain unchanged.
[0058] Comparative Examples 1-4
[0059] The amount (molar number) of calcium ions in Example 1 was changed from 75% to 10% of the total amount (molar number) of positive ions in the above two hyaluronates, and the others remained unchanged.
[0060] Comparative Examples 1-5
[0061] The amount (molar number) of calcium ions in Example 1 was replaced from 75% to 100% of the total amount (molar number) of positive ions in the above two sodium salts of hyaluronic acid, and the others remained unchanged.
[0062] Comparative Examples 1-6
[0063] The method described in step 6) of Example 1 is changed to the following, and the rest remains unchanged:
[0064] Mix 1 volume of 3% collagen and 1 volume of tyrosinase aqueous solution as much as that of colloidal solution A, the ratio of tyrosinase to collagen being 5U / g, and maintain the temperature at 0°C to 4°C for 48 hours to allow the collagen to be basically cross-linked, thereby obtaining solution P. Add solution P to colloidal solution E and mix well to obtain colloidal solution F.
[0065] Example 2
[0066] 1) Disperse sodium hyaluronate with a molecular weight of 2000 to 10,000 (Daltons) in water, add 10% calcium chloride salt solution, mix well, and replace 70% (molar number) of sodium ions with calcium ions to form colloidal solution A, in which the content or concentration of sodium hyaluronate is 17% wt / v;
[0067] 2) Add 0.5 times the molecular weight of 200,000-500,000 (Dalton) sodium hyaluronate solution to colloidal solution A, mix well, and obtain colloidal solution B, wherein the content or concentration of sodium hyaluronate in the above sodium hyaluronate solution is 8% wt / v;
[0068] 3) Add 5% diammonium phosphate solution to colloidal solution B, wherein the amount (molar number) of phosphate ions (or phosphorus) is 45% of the amount (molar number) of the above calcium ions, adjust the pH value to 10 to 11, mix well, and place in an environment with a temperature of 25-35° C. for 4 days to obtain colloidal solution C;
[0069] 4) Add 10% wt / v calcium chloride solution to colloidal solution C, wherein the amount (molar number) of calcium ions is 65% of the total amount (molar number) of positive ions in the above two hyaluronates, mix well, age at room temperature 25-35° C. for 6 days, and adjust the pH value to 6.8-7.2 to obtain colloidal solution D;
[0070] 5) Filter the colloidal solution D through a nanofiltration membrane with a pore size of 200 Da to remove small molecules, thereby obtaining a colloidal solution E;
[0071] 6) Add 0.5 times the volume of 7% collagen and 0.5 times the volume of tyrosinase aqueous solution in colloidal solution E to colloidal solution A, mix well, the ratio of the tyrosinase to the collagen is 10 U / g, keep the temperature at 0°C to 4°C for 24 hours, so that the collagen is basically cross-linked, and obtain colloidal solution F;
[0072] 7) The colloidal solution F is placed in a container so that the liquid layer thickness is 2 mm, and freeze-dried to remove the solvent.
[0073] Comparative Example 2-1
[0074] In Example 2, about 70% (in moles) of the sodium ions are replaced by calcium ions to form a colloidal solution A.
[0075] Replace with
[0076] About 100% (in moles) of sodium ions are replaced by calcium ions to form colloidal solution A.
[0077] and
[0078] A 5% solution of ammonium dihydrogen phosphate salt was added to the colloidal solution B, wherein the amount (molar number) of phosphate ions (or phosphorus) was the same as the amount (molar number) of phosphate ions (or phosphorus) in Example 2, and the others remained unchanged.
[0079] Comparative Example 2-2
[0080] The content or concentration of sodium hyaluronate in the sodium hyaluronate solution (200,000-500,000 Daltons) in Example 2 is replaced with a content or concentration of sodium hyaluronate in the sodium hyaluronate solution (200,000-500,000 Daltons) of 0.5% wt / v, and the rest remain unchanged.
[0081] As in Example 2-3
[0082] The content or concentration of sodium hyaluronate in the sodium hyaluronate solution (200,000-500,000 Daltons) in Example 2 is replaced with the content or concentration of sodium hyaluronate in the sodium hyaluronate solution (200,000-500,000 Daltons) being 18% wt / v, and the rest remain unchanged.
[0083] Comparative Example 2-4
[0084] The amount (molar number) of calcium ions in Example 2 was changed from 65% to 15% of the total amount (molar number) of positive ions in the above two hyaluronates, and the others remained unchanged.
[0085] Comparative Example 2-5
[0086] The amount (molar number) of calcium ions in Example 2 was replaced from 65% to 100% of the total amount (molar number) of positive ions in the above two hyaluronates, and the others remained unchanged.
[0087] Comparative Example 2-6
[0088] The method described in step 6) of Example 2 is changed to the following, and the rest remains unchanged:
[0089] Mix 0.5 times the volume of 7% collagen and 0.5 times the volume of tyrosinase aqueous solution as that of colloid solution A, the ratio of tyrosinase to collagen being 10U / g, and maintain the temperature at 0°C to 4°C for 24 hours to allow the collagen to be basically cross-linked to obtain solution P. Add solution P to colloid solution E and mix to obtain colloid solution F.
[0090] The method of the above sodium hyaluronate is as follows:
[0091] Dissolve the commercially available sodium hyaluronate with a molecular weight of 500,000-1,000,000 Daltons in a three-necked bottle, and uniformly add a solution of hydrogen peroxide and ascorbic acid in a molar ratio of 3:1 while stirring until the concentration of hydrogen peroxide is 2-4%, adjust the pH to 4, heat to 45-55°C in a water bath, and keep warm for 10-30 minutes, then add a 5% sodium hydroxide solution to the reaction solution, adjust the pH to 7-7.5, filter with nano (ultra) filtration membranes with pore sizes of 500,000 Daltons, 200,000 Daltons, 10,000 Daltons, and 2,000 Daltons, and intercept the solution containing sodium hyaluronate with a molecular weight of 200,000 Daltons-500,000 Daltons and 2,000 Daltons-10,000 Daltons; respectively, add acetone in a volume 2-3 times that of the reactant dropwise while stirring, leave overnight, filter out the degradation product by suction, wash with acetone, and dry under reduced pressure.
[0092] Test Example 1
[0093] The samples of the embodiment and the control example were cut into 2CM×1.5CM implant sponges and sterilized by γ-ray irradiation.
[0094] Animal in vivo toxicity tests, cytotoxicity tests, pyrogen tests, hemolysis tests, and intradermal injection experiments have shown that the implantable sponge is non-toxic, non-hemolytic, non-irritating, does not contain pyrogenic substances, has stable performance, and has good biocompatibility.
[0095] Treatment of apical cysts by simultaneous implantation of hydroxyapatite sponge after apical cyst removal
[0096] 882 patients with apical cysts were randomly divided into 1 experimental group and 6 control groups, with 126 cases in each group. After the apical cyst was removed, the sponges of the embodiment and the control were implanted in each group. After the implantation, the mucoperiosteum was repaired, the wound was sutured conventionally, and pressure bandage was applied. Antibiotics were used to prevent infection after the operation, and the sutures were removed after 7 days.
[0097] The patients were observed 1 week, 1, 3, and 6 months after surgery, and the treatment effect was recorded 6 months after surgery. Efficacy criteria: cured: X-ray showed that the apical shadow disappeared, the affected teeth were not loose, there was no percussion pain, and chewing returned to normal; improved: X-ray showed that the apical shadow was reduced or basically disappeared, the chewing function basically returned to normal, the affected teeth were slightly loose, the pain disappeared, and there was occasional slight discomfort; uncured: the apical area continued to swell or atrophy, the cyst recurred, the affected teeth were loose, the pain was unbearable, and all symptoms were not significantly improved, or even aggravated. Cure rate = number of cured cases / total number of cases × 100%. Failure rate = number of failed cases / total number of cases × 100%.
[0098] The results are shown in Table 1.
[0099] Table 1 Clinical experimental results of Example 1 and its control sample for treating apical cysts
[0100] Group Number of failures Number of cases improved Number of cured cases Cure rate (%) Failure rate (%) Example 1 4 18 104 82.5 3.2 Comparative Example 1-1 18 36 72 57.1 14.3 Comparative Example 1-2 24 32 70 55.6 19.0 Comparative Examples 1-3 29 35 62 49.2 23.0 Comparative Examples 1-4 21 37 68 54.0 16.7 Comparative Examples 1-5 34 32 60 47.6 27.0 Comparative Examples 1-6 39 31 56 44.4 30.9
[0101] The results showed that the cure rate of the example group was significantly higher than that of the control group, and the failure rate of the example group was significantly lower than that of the control group. The long-term overall effect of the example was better, with the advantages of long-term and high efficiency.
[0102] Test Example 2
[0103] The examples and control examples were implanted in the bone defect areas after the operations (the implant sponges were cut into 2CM×1.5CM size) in 122 cases of tooth extraction, 104 cases of apical capsule extraction, 83 cases of periodontitis flap surgery, 56 cases of apex resection, 66 cases of superior sinus perforation repair, 78 cases of dead bone extraction, and 56 cases of alveolar plasty.
[0104] Results After the sponge was implanted in the bone defect area, bleeding stopped quickly in the Example, and the average blood clot formation time in the Example was shortened by more than 50% compared with the control example.
[0105] Table 2 Average clot formation time of Example 2 and Control Example
[0106] Group Average clot formation time (s) Example 2 67 Comparative Example 2-1 168 Comparative Example 2-2 122 Comparative Example 2-3 305 Comparative Example 2-4 137 Comparative Example 2-5 226 Comparative Example 2-6 203
[0107] The results show that the embodiment takes effect faster than the control example, and has obvious advantages of rapid effect and high efficiency.
Claims
1. A method for preparing a highly efficient, fast-acting and long-acting hydroxyapatite implant sponge, the method comprising: 1) Disperse sodium hyaluronate with a molecular weight of 2000 to 10,000 Daltons in water, add calcium salt solution, mix well, and replace 40% to 70% of the molar amount of sodium ions with calcium ions to form colloidal solution A, wherein the content or concentration of sodium hyaluronate in the solution is 10-30% wt / v; 2) Adding 0.5-2 times the weight or volume of a sodium hyaluronate solution with a molecular weight of 200,000-500,000 Daltons to colloidal solution A to obtain colloidal solution B, wherein the content or concentration of sodium hyaluronate in the above sodium hyaluronate solution is 2-10% wt / v; 3) Add a solution of phosphate or hydrogen phosphate or dihydrogen phosphate or a mixed salt thereof to the colloidal solution B, wherein the molar amount of phosphate ions or phosphorus is 40% to 60% of the molar amount of the calcium ions, adjust the pH value to 10 to 11, mix well, and place in an environment at a temperature of 25-35° C. for 2-7 days to obtain a colloidal solution C; 4) Adding calcium salt solution to colloidal solution C, wherein the molar amount of calcium ions is 60% to 80% of the molar amount of total positive ions in the above two hyaluronates, mixing, aging at room temperature 25-35° C. for 2-7 days, adjusting the pH value to 6.8-7.2, to obtain colloidal solution D; 5) Filter the colloidal solution D through a nanofiltration membrane with a pore size of 200 Da to remove small molecular substances, thereby obtaining a colloidal solution E; 6) Add 0.5-2 times the volume of 1-10% collagen and 0.5-2 times the volume of tyrosinase aqueous solution as that of colloid solution A to colloidal solution E, mix well, the ratio of the amount of tyrosinase to the collagen is 1-15U / g, keep the temperature at 0°C to 4°C for 24-72 hours, so that the collagen is basically cross-linked, and obtain colloidal solution F; 7) The colloidal solution F is placed in a container so that the liquid layer thickness is 1-3 mm, and freeze-dried to remove the solvent.
2. The preparation method according to claim 1, characterized in that The content or concentration of sodium hyaluronate with a molecular weight of 2000 to 10,000 Daltons is 20-25% wt / v.
3. The preparation method according to claim 1, characterized in that The content or concentration of sodium hyaluronate with a molecular weight of 200,000-500,000 Daltons is 4-8% wt / v.
4. The preparation method according to claim 1, characterized in that The calcium salt includes calcium chloride, calcium acetate, calcium nitrate, calcium hydroxide or a mixture thereof.
5. The preparation method according to claim 1, characterized in that The phosphate, hydrogen phosphate or dihydrogen phosphate includes potassium salt, sodium salt and ammonium salt thereof.
6. The preparation method according to claim 1, characterized in that The molar amount of phosphate ions or phosphorus in the solution of the phosphate, hydrogen phosphate, dihydrogen phosphate or a mixed salt thereof is 50% to 55% of the molar amount of calcium ions.
7. The preparation method according to claim 1, characterized in that The aging time is 3-5 days.
8. The preparation method according to claim 1, characterized in that The thickness of the liquid layer is preferably 1-2 mm.
9. The preparation method according to claim 1, characterized in that The implant sponge is further prepared into a film, column, strip, plate, block, plug, pill, sheet, sponge or gel.